Exploring Capability Development for Technology Firms in Malaysia : A Case Study on the Growth Story of Datasonic Group Berhad - Lee, Stanley Chiang Fei (2015)
Datasonic Group Berhad was founded in 1980 and, over the course of the last three decades, has grown into a leading integrated ICT solutions provider in Malaysia. Datasonic is one of the key local players in the growing Malaysian smart card industry and has been instrumental in helping the Malaysian government to realise several national smart card initiatives (including the implementation of the Malaysian National E-ID Card, printing of the Malaysian Electronic E-Passport, and facilitating the nationwide migration to chip-based EMV credit cards). In this paper, the case study of Datasonic is used to describe the growth path of a latecomer technology firm, and understand its growth history within the business and competitive context of a less-developed country. We describe its growth in parallel with the macro-economic developments in Malaysia. We end with a summary of the key findings and managerial implications. Datasonic’s strategic choices and growth path is used to illustrate an alternate capability development model for latecomer firms in developing countries.